The effect of a cluster randomised control trial on objectively measured sedentary time and parental reports of time spent in sedentary activities in Belgian preschoolers: the ToyBox-study. Issue 1 (December 2016) - De Craemer, Marieke; De Decker, Ellen; Verloigne, Maïté; De Bourdeaudhuij, Ilse; Manios, Yannis; Cardon, Greet
Abstract Background In preschoolers, high levels of sedentary behaviour are associated with several adverse health outcomes. The purpose of this study is to report the effects of the ToyBox-intervention (a European 24-week cluster randomised controlled trial) on sedentary behaviour in preschoolers. Methods In Belgium, 859 preschoolers from 27 kindergartens (15 intervention and 12 control) wore an accelerometer to objectively measure their sedentary time and 1715 parents/caregivers completed a questionnaire to assess sedentary activities in which preschoolers participate at home. Main outcomes were objectively measured sedentary time, time spent watching TV, using the computer and time spent in quiet play. Multilevel repeated measures analyses were conducted to take clustering into account. Intention to treat analysis was used to handle missing data. Results A sample of 859 (29.5 % of all contacted children) preschoolers (4.4 ± 0.6 years, 54.4 % boys) provided valid accelerometer data at either baseline or follow-up and parents of 1715 (58.9 % of all contacted children) preschoolers (4.4 ± 0.5 years, 52.5 % boys) completed a questionnaire at either baseline or follow-up. No intervention effects were found on objectively and subjectively measured total sedentary time in the total sample. However, some effects on objectively and subjectively measured sedentary time were found in specific subgroups. Preschoolers from the intervention group from high SES kindergartens and preschoolers with high levels of sedentary time at baseline decreased their sedentary time, while preschoolers from the control group increased their sedentary time. Girls in the intervention group decreased their TV viewing time during weekend days (-5.83 min/day), while girls' &TV viewing in the control group increased (+4.15 min/day). In low SES kindergartens, a smaller increase for computer time during weekend days was found in preschoolers in intervention kindergartens (+6.06 min/day) than in control kindergartens (+12.49 min/day). Conclusion While some small positive effects were found in some sub-groups, the ToyBox-intervention had no effect on objectively and subjectively measured sedentary time in the total sample. A longer period to implement the intervention and a more active involvement of parents/caregivers might enhance intervention effects. The ToyBox-study is registered with the clinical trials registry clinicaltrials.gov, ID: NCT02116296.